The impact of inflation and GDP growth rate on unemployment in Egypt during the period 1991-2022 using the ARDL Model - soltani, ahlem fadila; Taleb, mohamd elamine oualid (Journal of Research in Finance and Accounting, 2024)
This study aims to identify the impact of inflation and GDP growth rate on unemployment rate in Egypt during the period 1991-2022 using ARDL model, to test short- and long-term effects. The study concluded that there is an inverse long-term relationship between unemployment and the GDP and that there is no long-term relationship between unemployment and inflation. The value of the error correction factor in the dynamic model also showed that the unemployment rate adjusts towards its equilibrium value in each period by 19.97%, meaning that the unemployment rate takes about five years to adjust towards its equilibrium value.